Treatment of inedible poultry carcasses through composting - Valente, Beatriz Simões; Xavier, Eduardo Gonçalves; Brum Júnior, Berilo de Souza; Anciuti, Marcos Antonio; Schiedeck, Gustavo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
A trial was conducted to evaluate the treatment of inedible poultry carcasses through composting. Physical and chemical transformations of biomass were monitored during 180 days of composting. A completely randomized design was used and data were subjected to ANOVA and polynomial regression at 5%. Moisture was not a conditioning factor for efficiency of second stage of composting, highlighting the significance of intermittent revolving of composting material. Poultry litter supplied nitrogen (N) for the microorganisms, hence should not be used as a carbon (C) source for composting of inedible poultry carcasses and must be replaced for materials containing a high C:N ratio. The mixture of inedible poultry carcasses and poultry litter resulted in a low initial C:N ratio, leading to volatilization of N and, as a consequence, increasing C:N ratio during the whole composting process. As a result, additional time was needed for proper stabilization of biomass. The final compost showed a high pH and therefore may be used for correcting acid soils. Composting process increased nutrients concentration in the biomass. The values herein obtained were within limits of environmental legislation of some countries, such as Brazil (Normative Instruction Nº25/2009). In conclusion, composting is an alternative for ecologically correct disposing of inedible poultry cuts and ought to be used for poultry producers and industry, helping achieving its environmental sustainability.